PENGATURAN HUKUM PENGEMBALIAN KERUGIAN KEUANGAN NEGARA ATAS TERDAKWA TINDAK PIDANA KORUPSI YANG MENINGGAL DUNIA - Muhammad Mashuri (MIMBAR YUSTITIA, 2020)
Refund of state financial losses related to accused corruption who died using civil instruments in an effort to recover losses. Efforts to recover financial losses of the state using civil instruments, are entirely subject to the discipline of material civil law as well as formil, although it relates to corruption crimes. Criminal proceedings follow a material evidentiary system while civil processes adhere to a formil evidentiary system that can be more difficult than material proof. The method used in this study is to follow the method of normative legal research by analyzing the regulation of the substance of the provisions on the procedure of returning state financial losses related to the accused of corruption crimes who died. In the event that the accused dies during the examination at the court hearing, while in real terms there has been a state financial loss, then the public prosecutor immediately submits a copy of the news file of the hearing to the State Attorney or submitted to the aggrieved agency for civil lawsuit against his heirs. After the court's decision that has obtained a permanent legal force, there are still property belonging to the convicted that is suspected to be derived from the proceeds of corruption crimes, civil lawsuits can be made against the convicted or his heirs.